Comparison of Value-Added Analysis of Coffee Processing with Different Market Orientations: (Case Study on Cooperative of Producer Coffee Margamulya). (June 2018) - Karyani, T; Djuwendah, E; Supriyadi, E
Abstract: Cooperative of Producer Coffee Margamulya (CPCM) consists of 140 members who produced Arabica java preanger coffee with an average of 70 tons green bean per year. The cherry coffee is first processed into green bean using wet processing method before being sold. Eighty percent of green beans are marketed to exporters (PT. Taman Delta Indonesia / PT. TDI) while 10% to Indocom and the other 10% to various markets with various products. This study was more focused on the analysis of difference of added value obtained by cooperatives from the dominant market for green bean, i.e., to exporters and Indocom. Also, this study aimed to determine the factors that influence market selection. The method used was a case study, with Hayami value-added analysis technique. The result showed that the added value of cherry processing became green bean for the export market was 19% while the value added for Indocom was 34%. The reason for choosing the market to exporters is that PT. TDI receives a large number of green beans, and provides UTZ (utilize) certification assistance. On the contrary, Indocom only bought smaller volumes than PT. TDI with non-fixed frequencies.